One summer day - Lewis, Kim, 1951- (Cambridge, Mass. : Candlewick Press, 1996)
Little Max wants a closer look at the huge red tractor which passes by his house, so when his friend takes him for a walk to watch it at work, he is delighted.
Keywords: Tractors -- Fiction; Walking -- Fiction; Summer -- Fiction